2015
DOI: 10.1016/j.jff.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Saponins isolated from the leaves of Panax notoginseng protect against alcoholic liver injury via inhibiting ethanol-induced oxidative stress and gut-derived endotoxin-mediated inflammation

Abstract: Available online A B S T R A C TEffects of saponins from leaves of Panax notoginseng (LPNS) against alcoholic liver injury were evaluated, and their probable molecular mechanisms were further elucidated in a mouse model of chronic-plus-single-binge ethanol feeding. Alcohol exposure dramatically increased plasma levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), triacylglycerol (TG) and endotoxin; these elevations were attenuated by treatment with LPNS at a dose of 100 or 300 mg/kg. LPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…Adanya kandungan terpenoid dan saponin menjadikan temu ireng berpotensi sebagai obat. Wang et al (2015) menunjukkan saponin berkhasiat sebagai antioksidan dan hepatoprotektor. Beberapa penelitian lain menunjukkan bahwa saponin berkhasiat juga sebagai antikanker (Man et al, 2015;Yuan et al, 2013), meningkatkan imunitas pada unggas (Yu et al, 2015a), antitumor (Yu et al, 2015b), dan imunomodulator (Nalbantsoy et al, 2012).…”
Section: Hasil Dan Pembahasanunclassified
“…Adanya kandungan terpenoid dan saponin menjadikan temu ireng berpotensi sebagai obat. Wang et al (2015) menunjukkan saponin berkhasiat sebagai antioksidan dan hepatoprotektor. Beberapa penelitian lain menunjukkan bahwa saponin berkhasiat juga sebagai antikanker (Man et al, 2015;Yuan et al, 2013), meningkatkan imunitas pada unggas (Yu et al, 2015a), antitumor (Yu et al, 2015b), dan imunomodulator (Nalbantsoy et al, 2012).…”
Section: Hasil Dan Pembahasanunclassified
“…The early stage of ALD is reflected as fatty liver, but it is finally progressing into more severe forms, such as inflammation, fibrosis, and cirrhosis [ 2 ]. Nowadays, ALD has become one of the leading causes of chronic diseases and death in the world [ 3 ]. Hence, it is necessary to unmask the pathological mechanisms of ALD and to look for potential therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicate that steatosis, oxidative stress, inflammatory factors, and mitochondrial dysfunction are involved in ALD [ 5 ]. And it is widely accepted that oxidative stress and inflammation are key mechanisms underlying the pathogenesis of ALD [ 3 ]. Reactive oxygen species (ROS), a highly reactive species of free radical, are known to play a dual role in living systems [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, pretreatment with PNS at the dosage of 45 mg/kg, but not 22.5 mg/kg, significantly increased ZO-1, occludin, and claudin-5 protein levels in the ischemic brain. Interestingly, it was reported that in a rat model of alcoholic liver disease, a high dosage of PNS remarkably normalized the degradation of ZO-1 and occludin in the intestine barrier [24]. It does indicate an internal consistency in the results since the fence-like tight junction disruption was usually initiated by leukocyte-endothelial interactions either in the gut [25] or in the brain [26].…”
Section: Discussionmentioning
confidence: 99%